Modification of heat-induced whey protein isolate hydrogel with highly bioactive glass particles results in promising biomaterial for bone tissue engineering. (July 2021) - Dziadek, Michal; Charuza, Katarzyna; Kudlackova, Radmila; Aveyard, Jenny; D'Sa, Raechelle; Serafim, Andrada; Stancu, Izabela-Cristina; Iovu, Horia; Kerns, Jemma G.; Allinson, Sarah; Dziadek, Kinga; Szatkowski, Piotr; et al.
Graphical abstract: Highlights: Newly formulated hydrogels made of whey protein isolate and bioactive glass were created. Heat-induced gelation technique used allowed generation of ready-to-use, sterile materials. Bioactive glass particles were homogenously distributed in the hydrogel matrix. Hydrogels showed a high capacity for mineralization and antioxidant activity. Materials were cytocompatible and supported MG-63 osteoblastic cell functions. Abstract: This study deals with the design and comprehensive evaluation of novel hydrogels based on whey protein isolate (WPI) for tissue regeneration. So far, WPI has been considered mainly as a food industry by-product and there are very few reports on the application of WPI in tissue engineering (TE). In this work, WPI-based hydrogels were modified with bioactive glass (BG), which is commonly used as a bone substitute material. Ready-to-use, sterile hydrogels were produced by a simple technique, namely heat-induced gelation. Two different concentrations (10 and 20% w/w) of sol–gel-derived BG particles of two different sizes (2.5 and <45 µm) were compared. µCT analysis showed that hydrogels were highly porous with almost 100% pore interconnectivity. BG particles were generally homogenously distributed in the hydrogel matrix, affecting pore size, and reducing material porosity. Thermal analysis showed that the presence of BG particles in WPI matrix reduced water content in hydrogels and improved their thermal stability. BG particles decreased enzymatic degradation of the materials. The materials underwent mineralization in simulated biological fluids (PBS and SBF) and possessed high radical scavenging capacity. In vitro tests indicated that hydrogels were cytocompatible and supported MG-63 osteoblastic cell functions.